2017
DOI: 10.1007/s10552-017-0924-9
|View full text |Cite
|
Sign up to set email alerts
|

Reliance on medicinal plant therapy among cancer patients in Jamaica

Abstract: A large proportion of Jamaican cancer patients use medicinal plants in self-medicating practices and their perceptions and habits need to be considered by physicians, in the design of safe and effective care regimes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
28
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 23 publications
1
28
0
2
Order By: Relevance
“…A Jamaican study investigating the perceptions of people diagnosed with cancer about self-medicating with medicinal plants found that 60% of the participants (n = 80) reported using A. muricata for the treatment of a range of cancers, predominately breast and prostate cancer. [5] Similar results were showed in specialty oncology clinics in Trinidad with A. muricata being used by 80.9% of people living with breast, prostate and colorectal cancer (n = 150). [6] In addition, results of a cross-sectional study suggest that 14% of liver cancer patients in Peru (n = 88) had taken A. muricata to manage their cancer-related symptoms.…”
Section: Introductionsupporting
confidence: 68%
See 1 more Smart Citation
“…A Jamaican study investigating the perceptions of people diagnosed with cancer about self-medicating with medicinal plants found that 60% of the participants (n = 80) reported using A. muricata for the treatment of a range of cancers, predominately breast and prostate cancer. [5] Similar results were showed in specialty oncology clinics in Trinidad with A. muricata being used by 80.9% of people living with breast, prostate and colorectal cancer (n = 150). [6] In addition, results of a cross-sectional study suggest that 14% of liver cancer patients in Peru (n = 88) had taken A. muricata to manage their cancer-related symptoms.…”
Section: Introductionsupporting
confidence: 68%
“…Currently, A. muricata is widely utilised by people diagnosed with cancer. A Jamaican study investigating the perceptions of people diagnosed with cancer about self‐medicating with medicinal plants found that 60% of the participants ( n = 80) reported using A. muricata for the treatment of a range of cancers, predominately breast and prostate cancer . Similar results were showed in specialty oncology clinics in Trinidad with A. muricata being used by 80.9% of people living with breast, prostate and colorectal cancer ( n = 150) .…”
Section: Introductionmentioning
confidence: 99%
“…In developing tropical countries including Africa, different parts of A. muricata are being used to treat conditions such as diabetes [ 53 , 54 ], coughs, skin diseases [ 55 ], and cancers [ 25 27 , 56 58 ]. Furthermore, in both Jamaica [ 59 ] and Trinidad [ 60 ], A. muricata is the most prevalently used herbal remedy in the treatment of most cancers. For example, in Jamaica, a large proportion of cancer patients use medicinal plants in self-medicating practices, with A. muricata being commonly used (along with Petiveria alliacea ) for treating breast and prostate cancers, respectively [ 59 ].…”
Section: Botanical Description and Distributionmentioning
confidence: 99%
“…Furthermore, in both Jamaica [ 59 ] and Trinidad [ 60 ], A. muricata is the most prevalently used herbal remedy in the treatment of most cancers. For example, in Jamaica, a large proportion of cancer patients use medicinal plants in self-medicating practices, with A. muricata being commonly used (along with Petiveria alliacea ) for treating breast and prostate cancers, respectively [ 59 ].…”
Section: Botanical Description and Distributionmentioning
confidence: 99%
“…From the same research, we also reported that 27% of Jamaican medicinal plant users take pharmaceutical drugs concomitantly. A survey of cancer patients attending the oncology and urology clinics at the University Hospital of the West Indies in Kingston, and two earlier surveys of Jamaican prescription drug users identified high levels of herb-drug use (80% [ 4 ] 80% [ 5 ] and 81% [ 6 ], respectively), while awareness of such herb-drug use amongst health care professionals was low across all four surveys (13% [ 5 ], 15% [ 4 ], 18% [ 6 ] and 19% [ 3 ], respectively). High levels of concomitant herb-drug use and low physician awareness are reported elsewhere.…”
Section: Introductionmentioning
confidence: 99%